Edukasi Jajanan Sehat Menggunakan Media Kincir Angka terhadap Peningkatan Pengetahuan, Sikap dan Perilaku Siswa - Mihzaluna _ Frisky; Elsa Yolanda Tanjung; Intan Maulani Munthe; Sri Ulina; Nada Amirah (Jurnal Kesehatan Lingkungan Mandiri, 2025)
The consumption of unhealthy snacks among junior high school students remains a significant issue that can impact health, including digestive disorders, obesity, and non-communicable diseases. Interactive health education is necessary to raise students' awareness in selecting safe and nutritious snacks. This study aimed to examine the effect of healthy snack education using the "number wheel" media on improving students’ knowledge, attitudes, and behaviors. This research employed a one-group pretest-posttest design with a quantitative approach involving 30 ninth-grade students of SMPN 1 Deli Tua selected through purposive sampling. The instruments used were questionnaires measuring knowledge (dichotomous scale), attitudes, and behaviors (Likert scale). Data analysis using the Wilcoxon test showed a significant improvement in knowledge (p = 0.000), attitude (p = 0.001), and behavior (p = 0.000) after the educational intervention. It can be concluded that healthy snack education using the number wheel media has been proven effective in improving the knowledge, attitudes, and behaviors of SMPN 1 Deli Tua students.